2011
DOI: 10.5194/ars-9-49-2011
|View full text |Cite
|
Sign up to set email alerts
|

Influences of weather phenomena on automotive laser radar systems

Abstract: Abstract. Laser radar (lidar) sensors provide outstanding angular resolution along with highly accurate range measurements and thus they were proposed as a part of a high performance perception system for advanced driver assistant functions. Based on optical signal transmission and reception, laser radar systems are influenced by weather phenomena. This work provides an overview on the different physical principles responsible for laser radar signal disturbance and theoretical investigations for estimation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
149
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 247 publications
(168 citation statements)
references
References 24 publications
1
149
0
1
Order By: Relevance
“…Backscatter from weather phenomena such as rain, fog, dust or snow may result in unwanted detections [16]. Lighting conditions may also hinder reliable detection, e.g.…”
Section: Lidarmentioning
confidence: 99%
See 2 more Smart Citations
“…Backscatter from weather phenomena such as rain, fog, dust or snow may result in unwanted detections [16]. Lighting conditions may also hinder reliable detection, e.g.…”
Section: Lidarmentioning
confidence: 99%
“…Before digital processing, the received signal is mixed down to an intermediate frequency (IF). After some manipulation, and assuming that high frequency terms are filtered out, the IF signal for the n th pulse is given by 16) where τ is the time-of-flight to the target and back, and c is the speed of propagation. It can be shown that the dominant frequency components in the mixed down IF signal are due to the time-of-flight and the Doppler shift induced by relative radial motion between the radar and the reflector.…”
Section: Fmcw Radar Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…To guarantee string stability and maintain the desired space, much research has been proposed in [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. As stated in [6], there have been two control strategies, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, these control methods suggested are not applicable to the APCS. Second, without considering the contingent failures might happen to the onboard sensors in practical cars for reasons such as poor visibility due to rain or sandstorm and interference of radar signals [16,17]. The combined actuator fault is the third aspect that may add to the limitations since the actuator failure will cause a wrong operation on the actuator speed growing or reducing.…”
Section: Introductionmentioning
confidence: 99%